Gérard Morisset (1898–1970) et le portrait au Québec : reflets d’un idéal canadien-français - Bouffard-Veilleux, Mickaël (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2009)
Gérard Morisset (1898–1970) can be numbered among the most important founders of Québec’s art history. This article highlights the ideology underlying Morisset's analyses and descriptions of French Canadian portraiture. Through a variety of texts published between 1936 and 1960, Morisset constructs a history of portraiture in the province, systematically using that history to praise a French Canadian national character. He claims to be able to read honesty, industry, simplicity and a "smiling bonhomie," not only in the facial features of French Canadian sitters but also in the brushstrokes of Québec’s francophone portraitists.